Contextualizing Teacher Efficacy in a High-Performing System: A Research Agenda. Issue 3 (3rd July 2017) - Wang, Li-Yi; Li, Jen-Yi; Tan, Liang-See; Lee, Ling
Abstract: Drawing from Albert Bandura's social cognitive theory, Tschannen-Moran, Woolfolk Hoy and Hoy (1998) proposed an integrated model of teacher efficacy to aid the understanding of this complex construct. This framework, despite its richness and usefulness in framing teacher efficacy research within the education landscape, is barely examined in the Southeast Asian education context. Acknowledging that teacher efficacy is a context-specific construct, this article discusses three defining features of the socio-cultural context in Singapore, including diversification of curriculum, high-stakes examinations and the culture of collectivism. We argue that these three features present a unique culturally appropriated perspective on the interpretation of Tschannen-Moran et al.'s integrated conceptual framework. These contextual characteristics and their implications to choices of methodological inquiries need to be considered in the application of this influential framework to teacher efficacy research across subject matters, levels and academic streams in Singapore as well as other education systems that share similar socio-cultural backgrounds.